INTERNATIONAL CONFERENCE ON THE THREE PILARS OF ASEAN COMMUNITY DEVELOPMENT, 3-4 OCTOBER 2017 MERAJUT ASA DALAM : KEKERABATAN DAN KERJASAMA SOSIAL BUDAYA KHAS BANGSA-BANGSA ASEAN - B. Sulistiyono, Bambang (JURNAL ILMIAH M-PROGRESS, 2017)
The existence of ASEAN trully did not comes apart from concerns about the South East Asian Nations which has conflicted, for example like the confrontation between Indonesia and Malaysia, territorial demand between Phillipine and Malaysia on Sabah, also the separation of Singapore from the Malaysian Federation. From those backgrounds, the South East Asian Nations especially Indonesia and Malaysia which recently conflicted, realizes the needs to form a cooperation to reduce tension, to construct confidence building and pushing regional cooperation growth which felt have no progress after each nations receive its independence. 8 August 1967 is the first ASEAN formation spearheaded by five Ministers of Foreign Affair from Indonesia, Phillipine, Malaysia, Singapore and Thailand, which resulted in the signation of ASEAN Declaration or known as The Bangkok Declaration and it also means ASEAN is formally created. One of the ASEAN's aim is "to accelerate economic growth, social progress and cultural growth in South East Asia Nations." Nevertheless, in actualizing ASEAN's growth it is not as easy as turning the palm of a hand, various national interest affected ASEAN's policy. Resulted to outdraw the main aim that have been agreed by the Nations, informal or formal conflict always happened in the middle of goverments effort in reducing conflict. For example, the arrest of KPLP Indonesian Officer by the Malaysian Royal Police, the accusation of Thailand to Malaysia in helping separatism of South Thailand, the dispute of Angkor Temple between Cambodia and Vietnam constituted on how the implementation of ASEAN's agreements are hard to happened. Although, the interesting parts are eventhough conflicts still exist between each Nations but open war which can cause many victims never happens. One of the secret why ASEAN Nations stays solid is the tolerance and togetherness underlied the brotherhood of South East Asia Nations. Which nowadays had been used as a strong reason to build trush building between each member for the advancement of ASEAN nations in the future. Social and cultural approaches through public diplomation, reconsiliation and bridging of kinship always be a reference in problem solutions, relativeness in ASEAN's history had always be an important point for ASEAN's progress until nowadays. Keywords : Cooperation, Kinship And Prospective